Diversity and distribution of ferns in forest over limestone in Cebu Island Key Biodiversity Areas (KBAs), Philippines - Edgardo Lillo; ARCHIEBALD B. MALAKI; STEVE MICHAEL T. ALCAZAR; RAAMAH ROSALES; BERNARDO R. REDOBLADO; ERWIN PANTINOPLE; RITCHE U. NUEVO; ROBERTO C. CUTILLAR; ARNALDO ALMIRANTE (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lillo EP, Malaki AB, Alcazar SMT, Rosales R, Redoblado BR, Pantinople E, Nuevo RU, Cutillar RC, Almirante A, Buot IE Jr. 2020. Diversity and distribution of ferns in forest over limestone in Cebu Island Key Biodiversity Areas (KBAs), Philippines. Biodiversitas 21: 413-421. Three forest areas of Cebu Island, Philippines were recognized as Key Biodiversity Areas (KBAs) by Department of Environment and Natural Resources [DENR], Philippines based on the criteria of vulnerability and irreplaceability, namely Nug-as of Alcoy, Palinpinon Range of Dalaguete, and Mt. Lantoy of Argao. The study aimed to assess the composition, diversity, and distribution of ferns in the aforementioned KBA's. Quadrat at 20 m x 20 m was established within the 2000 m transect line at an interval of 200 m. Result showed a total of 50 species, categorized into 15 families and 29 genera for 30 quadrats. Twelve species were considered as new records on Cebu. Thirteen species were recorded in both Mt. Lantoy and Nug-as forest KBA’s, but absent in Palinpinon range. While 6 species were recorded as unique to Nug-as forest. Nug-as forest and Mt. Lantoy showed a relative value of very high species diversity. Nug-as forest and Mt. Lantoy KBA forming into one cluster and Palinpinon range proved to have a distinct fern species composition, and form another cluster. Local government units (LGU) in every KBA need to recognize the necessity of biodiversity information in their localities that would facilitate information sharing and awareness, hence enhancing protection and conservation of unique biodiversity, since they are at the forefront of local action.